2010
DOI: 10.4196/kjpp.2010.14.6.365
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Induces Apoptotic Cell Death via p53 in LNCaP Cells

Abstract: In this study, we examined whether melatonin promotes apoptotic cell death via p53 in prostate LNCaP cells. Melatonin treatment significantly curtailed the growth of LNCaP cells in a dose-and time-dependent manner. Melatonin treatment (0 to 3 mM) induced the fragmentation of poly(ADPribose) polymerase (PARP) and activation of caspase-3, caspase-8, and caspase-9. Moreover, melatonin markedly activated Bax expression and decreased Bcl-2 expression in dose increments. To investigate p53 and p21 expression, LNCaP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
(32 reference statements)
2
35
0
Order By: Relevance
“…Most importantly, this does not pair with p53-mediated pro-survival effects, as melatonin does not counteract apoptosis induced by chemotherapy (Supplementary Figures S2 and S3A-D). One study demonstrated that 1 mM melatonin induces p53 phosphorylation at Ser-15 and apoptosis in androgensensitive LNCaP prostate cancer cells (Kim and Yoo, 2010). The concentration of melatonin used in this study is far higher than both physiological levels (1 mM vs 1 nM) and levels reached when melatonin is used to treat sleep disorders or as an adjuvant for anticancer therapy (Vakkuri et al, 1985;Kane et al, 1994;Markantonis et al, 2008), in which the highest concentration is 0.5 mM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most importantly, this does not pair with p53-mediated pro-survival effects, as melatonin does not counteract apoptosis induced by chemotherapy (Supplementary Figures S2 and S3A-D). One study demonstrated that 1 mM melatonin induces p53 phosphorylation at Ser-15 and apoptosis in androgensensitive LNCaP prostate cancer cells (Kim and Yoo, 2010). The concentration of melatonin used in this study is far higher than both physiological levels (1 mM vs 1 nM) and levels reached when melatonin is used to treat sleep disorders or as an adjuvant for anticancer therapy (Vakkuri et al, 1985;Kane et al, 1994;Markantonis et al, 2008), in which the highest concentration is 0.5 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin treatment induces the accumulation of heavily phosphorylated p53 protein (Kim and Yoo, 2010). This occurs at a specific p53 residue (Ser-15) (Kim and Yoo, 2010) that has been shown to have a critical role in orchestrating p53-reponse upon DNA-damaging agents (Lakin and Jackson, 1999;Helton and Chen, 2007). In response to DNA damage, different kinases, including ATM and p38 MAPK, phosphorylate p53 at Ser-15 residue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serine 15 of p53 has been reported to be a key phosphorylation target during DNA damage (Santoro et al, 2012). Melatonin was found to induce apoptosis by phosphorylating p53 at serine 15 and increasing the expression of downstream signals such as Mdm2 and p21 in LNCaP human prostate cancer cells (Kim and Yoo, 2010).…”
Section: Introductionmentioning
confidence: 99%